Parents' Inadequate Estimate of Their Children's Objectively Physical Activity Level - Karin Kippe; Adilson Marques; João Martins; Pål Arild Lagestad (MDPI AG, 2022)
This study aimed to investigate parents' estimation of their preschool children's leisure-time physical activity (PA) and the correlation between parents' reported participation in PA with their children in leisure time and their children's PA levels. A total of 244 Norwegian preschool children aged 4-6 and their parents were enrolled in the study. According to standard protocols, the children's PA level was measured with Actigraph GT1M accelerometers. The parents completed a questionnaire that provided information about their estimation of their children's PA and their reported participation in their children's PA. Correlation analyses and scatter plots showed no significant association between parents' estimation of their children's PA level at leisure time and the children's objectively measured PA level. Only 5% of the parents estimated their children's PA level correctly. In general, the parents overestimated their children's PA levels by three times. Furthermore, the results found no significant correlation between children's PA levels at leisure time and parents' reported participation in PA with their children. Our findings indicate that parents' self-estimation of their children's PA is inaccurate, which is problematic. Considering that the PA levels of many children are too low to fulfill internationally established health recommendations, parents' 'wrong' perception about their children's PA urgently needs to be addressed and rectified.